Characterization of odorants in waxes for hot melt adhesives using sensory and instrumental analyses - Denk, Philipp; Ortner, Eva; Büttner, Andrea (International Journal of Adhesion and Adhesives, 2019)
Waxes are important additives in hot melt adhesives for improving the properties of the final product such as the melting point or viscosity. Up to one third of the formulation of the final product consists of waxes. For this purpose usually polyethylene (PE) waxes or Fischer-Tropsch (FT) waxes are used. Waxes affect the overall smell of hot melt adhesives, and often in a negative way. In our study the overall odor of five different waxes made by different manufacturing methods was characterized in order to classify the samples according to their overall smell. First of all the samples were evaluated by a trained sensory panel at room temperature and after heating to 80 °C using descriptive analyses. Then the volatiles responsible for the overall smell of the samples were directly extracted using thermal desorption in combination with cryo-focusing and analyzed by gas chromatography-mass spectrometry-olfactometry (GC-MS/O). Moreover, the volatiles in the waxes were recovered using solvent extraction and isolated by solvent assisted flavour evaporation (SAFE). The most dominant odorants were then characterized by GC-O and odor extract dilution analysis (OEDA). Using these approaches 39 odorants having different chemical structures were successfully identified for the first time in waxes used as additives in hot melt adhesives. These odorants included alcohols with tallowy, soapy odor qualities such as 2-methyl-2-decanol, 2-methyl-2-dodecanol, and 1-undecanol, as well as a range of lactones such as γ-decalactone and γ-undecalactone having soapy, peach-like odor descriptions. The attributes of the odorants detected using GC analyses correlated with the descriptive analyses of the human sensory panel. This study indicates that the odor impact of waxes to hot melt adhesives depends on the manufacturing method of each single wax and that there is no clear trend for the preferential usage of PE or FT waxes.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Gas chromatography; Hot melt; Mass spectrometry; Odor; Olfactometry; Wax